A New Comprehensive Model to Simulate and Optimize Fluid Flow in Complex Well‐Formation System for In Situ Leaching Uranium - Zhaokun Li; Xuebin Su; Yangquan Jiao; Yu Zhang; Yang Qiu; Xiaodong Hu (Energy Science & Engineering)
ABSTRACT In situ leaching (ISL) is an important method for green and efficient development of sandstone‐type uranium ore. It achieves ISL of uranium through the deployment of injection and extraction vertical well patterns. The optimization of parameter matching between injection and extraction wells is key to improving the efficiency of uranium development. However, as the depth of mining and the scale of development increase, the small area controlled by vertical wells leads to a large number of vertical wells and high drilling costs, which severely affect the benefits of mine development. In this paper, taking the development case of the LK mine area in Xinjiang as an example, an extraction method of “horizontal well injection–vertical well extraction” was innovatively proposed for the first time. By using the well‐storage coupling model and particle tracking technology, this study systematically investigated the impact of well types and injection–extraction parameters on the leaching range and the distribution of leaching dead zones. Furthermore, a hybrid multiobjective optimization algorithm was used to complete the parameter optimization of well‐storage coupling for ISL of uranium. The research content of this paper explores the impact of injection–extraction parameters and well spacing on the leaching effect of “horizontal well injection–vertical well extraction,” providing a method and approach for the optimization study of ISL uranium parameters. In addition, the research results of this paper have certain guiding significance for enhancing the leaching and extraction effect of the existing uranium mining plan in the LK mining area.